2015
DOI: 10.1371/journal.pone.0145622
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Value of IFN-Lambda3 and IFN-Lambda4 Genotyping in Patients with Chronic Hepatitis C (CHC) Genotype 2/3 in a Real World Setting

Abstract: BackgroundSNPs near the interferon lambda (IFNL) 3 gene are predictors for sustained virological response (SVR) in patients with chronic hepatitis C genotype (GT) 1. In addition, a dinucleotide frame shift in ss469415590 was described, which generates IFNL4. In this study, we compared the role of IFNL4 variants with IFNL3-(rs12979860) and IFNL3-(rs8099917) on response to pegylated (PEG)-IFN and Ribavirin (RBV) in patients with chronic hepatitis C GT2/3.MethodsWe recruited 1006 patients with chronic hepatitis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that IFNL4 polymorphisms are a predictor of treatment response with interferon-based regimens with genotype 2 and 3 as well as for simeprevir and interferon-based therapy for genotype 1 [7–9]. In addition, polymorphisms in both IFNL3 and IFNL4 have been shown to be associated with high serum and hepatic iron concentrations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that IFNL4 polymorphisms are a predictor of treatment response with interferon-based regimens with genotype 2 and 3 as well as for simeprevir and interferon-based therapy for genotype 1 [7–9]. In addition, polymorphisms in both IFNL3 and IFNL4 have been shown to be associated with high serum and hepatic iron concentrations [10].…”
Section: Introductionmentioning
confidence: 99%